2007
DOI: 10.1177/0143034307085660
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Learning Approaches in Students from the USA, Japan and Taiwan

Abstract: The purpose of this study is to examine the relationship between approaches to learning and locus of control of students from the USA, Japan, and Taiwan. The results show that students from the USA utilized more rote memory learning compared to students from Japan and Taiwan, while students from Japan were more likely to be `Achieving' learners than peers from either the USA or Taiwan. `Deep Approaches' to learning, however, were similar across the three groups. Students from both Japan and Taiwan exhibited hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This tendency toward externality in Asia could also be influenced by the overall religious/philosophical beliefs exemplified in Buddhism and some other belief systems which postulate the importance of accepting ones circumstances. In a different study of Asian and American cultures, Brown, Aoshima, Bolen, Chia, and Kohyama (2007) compared locus of control and learning approaches among students in the United States, Japan, and Taiwan. They found that both Japanese and Taiwanese students scored higher on externality than the students from the United States but that they are not more likely to attribute learning outcomes to external versus internal factors.…”
Section: Locus Of Controlmentioning
confidence: 99%
“…This tendency toward externality in Asia could also be influenced by the overall religious/philosophical beliefs exemplified in Buddhism and some other belief systems which postulate the importance of accepting ones circumstances. In a different study of Asian and American cultures, Brown, Aoshima, Bolen, Chia, and Kohyama (2007) compared locus of control and learning approaches among students in the United States, Japan, and Taiwan. They found that both Japanese and Taiwanese students scored higher on externality than the students from the United States but that they are not more likely to attribute learning outcomes to external versus internal factors.…”
Section: Locus Of Controlmentioning
confidence: 99%
“…A few earlier studies documented that Asians, Asian Americans, and MexicanAmericans had a more internal locus of control than their Caucasian counterparts (Brown et al 2007;Hamilton et al 1989;Si et al 1995). A number of studies, however, showed that ethnic minority groups such as African, Asian, and Mexican-Americans tended to hold a more external locus of control (Leung 2001;O'Hea et al 2009;Okeke et al 1999;Ramirez 1988) than European Americans.…”
Section: Introductionmentioning
confidence: 98%
“…Such results are consistent with fatalistic beliefs that prevail in many Asian cultures and the Catholic tradition in Mexican culture (McCabe, Goehring, Yeh, & Lau, 2008; Norenzayan & Lee, 2010). However, other research found that Asian American youth, who strongly valued education, were likely to attribute academic success and failure to their own efforts, reflecting an internal locus of control (Brown, Aoshima, Bolen, Chia, & Kohyama, 2007).…”
Section: Country Of Origin and Socioemotional Well-being Of Children ...mentioning
confidence: 99%